Faktor-Faktor yang Mempengaruhi Mahasiswa Lebih Memilih Uang Digital Dibanding Uang Tunai - Kamal, Laila; Hanum, Inas Mutiara (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to determine the factors that cause Surabaya students to prefer using digital money as a substitute for cash. Although the use of digital money has not been able to completely replace cash payments, the use of digital money is increasing every year. The study uses a quantitative research method using a survey. The results show that convenience, security and efficiency have a significant effect on increasing the use of digital money. Students are one of the large populations that use digital money, because students easily accept technological developments, especially the development of digital payments. Surabaya is a big city whose population uses a lot of digital money and there are many universities.